Tinjauan Filsafat Rekonstruksionisme Theodore Brameld dalam Implementasi Ekstrakurikuler E-Sport bagi Perkembangan Karakter Siswa - Lahope, Teofilus Adiwijaya; Laurensius, Agnes; Telaumbanua, Darni Putriani; Angelina, Maria; Sabelau, Mersi Deviana (Jurnal Christian Humaniora, 2024)
This research uses a descriptive qualitative method approach that aims to analyse and contribute Theodore Brameld's reconstructionist philosophical views on the assessment and use of electronic sports in formal educational institutions. The results of this study show the effectiveness of E-Sport as a school extracurricular can foster attitudes of solidarity, leadership, time management, sportsmanship, and form a good work ethic. On the other hand, the implementation of E-Sport should receive ethical guidance and supervision from various educational stakeholders, so that educational goals can be achieved optimally.